Punishment Analysis at School Based on Article 54 of the Child Protection Act in Law Number 35 of 2014 - Hotma Siregar; Atika Rahmi (BIRCU, 2019)
The purpose of this study, to adjust the form of regulations made by schools with the provisions of Law Number 35 of 2014 concerning Child Protection. Research conducted is qualitative research by conducting documentation and observation studies to obtain more accurate data. Documentation study is conducted to study and analyze the contents of the regulations that were applied in SMP 2 Helvetia. Observations are made to the school to see firsthand whether sanctions against violations of the rules given to students are in accordance with the Article 54 of the Child Protection Act. The results of this study, designed a form of regulation that will be applied in schools, where the punishment given in the event of a violation by students must be humane and still protect the rights of the child. If viewed from the provisions of Article 54 of Law Number 35 of 2014 concerning Child Protection, then the execution of the Punishment in SMP PAB 2 Helvetia does not violate the provisions of Article 54 of Law Number 35 of 2014, where the child is in an educational unit (school ) has been protected from acts of physical and psychological violence, this is evidenced by the absence of physical punishment in the school environment and the enactment of a point system which means that teachers and other education personnel have sought ways to punish students who violate the rules clearly and to avoid physical punishment.